Socialization of SIA to Bank Mandiri Customers MBKM Student Internship Indo Global Mandiri University - Erin, Arif Kurnia; Hertati, Lesi; Terrtiavini, Terrtiavini; Heryati, Agustina; Cahyani, Nani; Puspitawati, Lilis (International Journal of Social Science and Community Service, 2024)
Socialization of the PKM SIA program to Bank Mandiri customers through the MBKM program provides a positive contribution in increasing customer understanding of SIA and its benefits in the banking context. Students who took part in the internship program reported an increase in their understanding of the importance of AIS in supporting sound banking decisions. Several challenges related to the effectiveness of SIA socialization through PKM were also identified, such as time constraints and varying levels of understanding among customers. Therefore, it is recommended that PKM continue to improve their outreach methods, including the use of information and communication technology, as well as holding additional training sessions to ensure that customers can make maximum use of AIS.